2022
DOI: 10.3390/microorganisms10040734
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Analysis of Resilience of the Oral Microbiome in Allogeneic Stem Cell Transplant Recipients

Abstract: Stem cell transplantation (SCT) is associated with oral microbial dysbiosis. However, long-term longitudinal data are lacking. Therefore, this study aimed to longitudinally assess the oral microbiome in SCT patients and to determine if changes are associated with oral mucositis and oral chronic graft-versus-host disease. Fifty allogeneic SCT recipients treated in two Dutch university hospitals were prospectively followed, starting at pre-SCT, weekly during hospitalization, and at 3, 6, 12, and 18 months after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…These changes in the early post-transplant period may be due to a significant reduction in defense mechanisms due to the conditioning regimen and associated neutropenia, and they may also be related to OM, antibiotic use, and decreased oral intake. Previous studies have shown that these changes return to approximately the pre-conditioning phase within 1-3 months (134,138).…”
Section: Oral Microbiota and Hsctmentioning
confidence: 87%
See 1 more Smart Citation
“…These changes in the early post-transplant period may be due to a significant reduction in defense mechanisms due to the conditioning regimen and associated neutropenia, and they may also be related to OM, antibiotic use, and decreased oral intake. Previous studies have shown that these changes return to approximately the pre-conditioning phase within 1-3 months (134,138).…”
Section: Oral Microbiota and Hsctmentioning
confidence: 87%
“…Ulcerative oral mucositis after allogeneic HSCT has been observed only in the combination of multi-antibacterial therapy ( 133 ). In the analysis of oral rinses in patients undergoing allogeneic HSCT, the OM-affected group showed a substantial decrease in bacterial microbiota compared to the non-affected group for up to 3 weeks after transplantation ( 134 ). When neutrophil count was included in the regression model, it was found to be a confounding variable, affecting both mucositis and bacterial diversity, while there was no direct effect on diversity.…”
Section: Oral Microbiota and Hsctmentioning
confidence: 99%
“…Although several dozen core bacterial genera inhabit all oral compartments, different species occupy each oral niche, meaning oral microbes are site-specialists that compose distinct microbiotas in each oral environment [1,59]. We and others have previously reported the impact of allo-HSCT in oral microbiotas and their associations with allo-HSCT complications and outcomes [22][23][24][25][26]30]. However, these studies analyzed single oral sites and were mostly limited to the peri-engraftment period of allo-HSCT.…”
Section: Discussionmentioning
confidence: 99%
“…Since the immune system regulates microbiota composition [16] and chemotherapy [17], radiotherapy [18], and antibiotics [19] have detrimental effects on the microbiota, drastic alterations in the gut microbiota have been reported in allo-HSCT recipients, including loss of bacterial diversity and blooms of potentially pathogenic species [20]. Recent evidence shows these alterations extend to other microbiotas [21], including the relatively more stable oral microbiota [22][23][24][25][26]. More importantly, the pre-transplant microbiota and the extent of microbiota damage during allo-HSCT are associated with allo-HSCT complications and outcomes, so that gut and oral microbiota provide biomarkers in the allo-HSCT setting [24,25,[27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation